2017
DOI: 10.1039/c7ra02185b
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation and release of Beauveria bassiana from alginate–bentonite nanocomposite

Abstract: The present manuscript brings new information regarding the advantages of the encapsulation of B. bassiana in alginate matrices containing bentonite, such as conidia protection, swelling degree, and release kinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…It showed that crystallinity of SiO 2 turned to amorphous nature [88,96,102] as similar observation made by us in our previous work [93,94] . Other diffraction peaks of bentonite observe at 2θ=19.9 ° , 26.6 ° , 28.58 ° , 36.0 ° , 42.5 ° and 61.7 ° [103–106] . The peaks at 2θ=20.91 ° , 26.6 ° , 36.0 ° and 42.5 ° reflect that bentonite contains ample amount of quartz and no peak has seen at 31.30° represent for cristobalite [103] .…”
Section: Resultssupporting
confidence: 85%
“…It showed that crystallinity of SiO 2 turned to amorphous nature [88,96,102] as similar observation made by us in our previous work [93,94] . Other diffraction peaks of bentonite observe at 2θ=19.9 ° , 26.6 ° , 28.58 ° , 36.0 ° , 42.5 ° and 61.7 ° [103–106] . The peaks at 2θ=20.91 ° , 26.6 ° , 36.0 ° and 42.5 ° reflect that bentonite contains ample amount of quartz and no peak has seen at 31.30° represent for cristobalite [103] .…”
Section: Resultssupporting
confidence: 85%
“…After encapsulation, it is important to evaluate the release kinetics of the compound and for this a template was used as described by Batista et al (2017). The release kinetics assay showed us how the fungus release from the calcium alginate microparticles in the presence or absence of ultraviolet light.…”
Section: Discussionmentioning
confidence: 99%
“…The fungus had a larger release area when encapsulated and exposed to UV, this happened due to the fact that the microparticle system used in this work is effective in protection, especially in dry microparicles. Batista et al (2017) evaluated the growth areas of the Beauveria bassiana fungus encapsulated in alginate-bentonite microparticles dried using different air flow and lyophilization processes. The results showed that the light emission was directly related to the development of the organism and that the growth area was larger when the microparticles were dried by the air flow method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations